Salicylic acid improving salinity tolerance by enhancing photosynthetic capacity, osmotic adjustment and maintenance of Na+/K+ homeostasis in faba bean seedlings - Yuanyuan Ma; Zhi Wang; Bingyue Zhou; Wenhuan Yang; Yuping Wang (Chemical and Biological Technologies in Agriculture)
Abstract Background Salinity stress is a critical abiotic factor that significantly impairs crop productivity. Salicylic acid (SA) demonstrates efficacy in mitigating salt stress induced physiological damage across plant tissues. However, the physiological mechanism by which SA alleviates salinity stress in faba bean remains largely unclear. For this purpose, two genotypes of faba bean were subjected to various concentrations of NaCl and SA treatments design. Results Salt stress significantly reduced faba bean seedling growth, root architecture, biomass accumulation, and chlorophyll content, ultimately impairing photosynthetic efficiency and reducing yield compared to control plants. However, under 150 mmol L−1 NaCl treatment, chlorophyll a/b ratios, intercellular CO2 concentration (C i ), non-photochemical quenching (NPQ) of photosystem II (PSII), soluble protein (SP) content, soluble sugar (SS) content, and Na+ accumulation in both leaves and roots were markedly elevated compared to controls. The light utilization efficiency of PSII (Fv/Fm, ΦPSII, qP), gas exchange parameters (P n , G s , T r ) and contents of SP and SS content increased under the 1.0 mmol L−1 SA + NaCl treatment when compared to the NaCl treatment alone. SA also significantly inhibited Na+ uptake and enhanced the absorption of K+, Mg2+, Ca2+, and increased the K+/Na+ ratio in both roots and leaves of faba bean plants by up-regulating the expression of VfNHX1, VfSOS1, and VfHKT1 under NaCl stress. Moreover, exogenous SA also enhanced the 100-grain weight and pod-setting ability in salt-exposed faba bean plant. Conclusion Exogenous SA improved the tolerance of faba bean plants to salinity stress by enhancing PSII light utilization efficiency, osmotic adjustment, root system architecture, and maintaining Na+/K+ homeostasis. Graphical Abstract